Effects of infusion of GnRH pulses and level of body condition on ovarian function in postpartum beef cows - Andrade, L.P. (2013)
An experiment was conducted to test the hypothesis that postpartum anoestrus in beef cows is prolonged in cows in low condition (BC) because they have a reduced LH pulse frequency compared with cows in high BC.